2015
DOI: 10.1145/2700399
|View full text |Cite
|
Sign up to set email alerts
|

Universal and Distinct Properties of Communication Dynamics

Abstract: With the advancement of information systems, means of communications are becoming cheaper, faster and more available. Today, millions of people carrying smart-phones or tablets are able to communicate at practically any time and anywhere they want. Among others, they can access their e-mails, comment on weblogs, watch and post comments on videos, make phone calls or text messages almost ubiquitously. Given this scenario, in this paper we tackle a fundamental aspect of this new era of communication: how the tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…This distribution seems to appear due to various actions of normal users in shopping such as finding items, examining items, and comparing their prices. Indeed, we confirmed that IATs in CSS follow the log-logistic distribution, well modeled by odds ratio power law, which also coincides with existing theories found in human communication dynamics such as e-mail and SMS communications [7].…”
Section: Inter-arrival Time Differencesupporting
confidence: 90%
“…This distribution seems to appear due to various actions of normal users in shopping such as finding items, examining items, and comparing their prices. Indeed, we confirmed that IATs in CSS follow the log-logistic distribution, well modeled by odds ratio power law, which also coincides with existing theories found in human communication dynamics such as e-mail and SMS communications [7].…”
Section: Inter-arrival Time Differencesupporting
confidence: 90%
“…Due to the generic nature of the problem, several statistical tools have been developed for estimating IET distributions for renewal processes [34][35][36][37][38][39][40]. Additionally, some techniques based on survival analysis and event-history analysis have been used to analyze temporal network data [41][42][43]. Similar problems have also been encountered when analyzing geological data [44,45] and estimating inter-spike intervals of firing neurons [46].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the odds ratio is particularly good at capturing differences between distributions at small values of τ [45].…”
Section: Fitting Of the Emm To The Individual With The Largest Number Of Events And Comparison With Power-law Distributionsmentioning
confidence: 99%